Penile Metastasis as the First Manifestation of Sarcomatoid Renal Cell Carcinoma - Camlidag, Ilkay; Danaci, Murat; Nural, Mehmet Selim (Galenos Yayincilik, 2016)
…
Keywords: Penile Metastasis; Renal Cell Carcinoma; Sarcomatoid